2010
DOI: 10.1128/jvi.01334-09
|View full text |Cite
|
Sign up to set email alerts
|

Early Events in Kaposi's Sarcoma-Associated Herpesvirus Infection of Target Cells

Abstract: Kaposi's sarcoma-associated herpesvirus (KSHV), the most recently identified member of the herpesvirus family, infects a variety of target cells in vitro and in vivo. This minireview surveys current information on the early events of KSHV infection, including virus-receptor interactions, involved envelope glycoproteins, mode of entry, intracellular trafficking, and initial viral and host gene expression programs. We describe data supporting the hypothesis that KSHV manipulates preexisting host cell signaling p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
190
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 143 publications
(196 citation statements)
references
References 59 publications
(220 reference statements)
6
190
0
Order By: Relevance
“…KSHV attachment to the HMVEC-d cell surface occurs via heparan sulfate (HS) followed by temporal interactions with integrins (α3β1, αVβ3, and αVβ5) and the transporter xCT molecule. KSHV binding to these molecules results in the induction of FAK, Src, PI3-K, Rho-GTPases, Dia-2, PKC-ζ, ERK1/2, and NF-κB signal molecules (3)(4)(5)(6)(7)(8). Our studies using chemical inhibitors, dominant negative proteins, or cells lacking these molecules have shown that FAK, Src, PI3-K, and RhoA activation is necessary for KSHV entry (3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 73%
See 4 more Smart Citations
“…KSHV attachment to the HMVEC-d cell surface occurs via heparan sulfate (HS) followed by temporal interactions with integrins (α3β1, αVβ3, and αVβ5) and the transporter xCT molecule. KSHV binding to these molecules results in the induction of FAK, Src, PI3-K, Rho-GTPases, Dia-2, PKC-ζ, ERK1/2, and NF-κB signal molecules (3)(4)(5)(6)(7)(8). Our studies using chemical inhibitors, dominant negative proteins, or cells lacking these molecules have shown that FAK, Src, PI3-K, and RhoA activation is necessary for KSHV entry (3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 73%
“…Our studies using chemical inhibitors, dominant negative proteins, or cells lacking these molecules have shown that FAK, Src, PI3-K, and RhoA activation is necessary for KSHV entry (3)(4)(5)(6)(7)(8). Microtubule acetylation by RhoA-GTPase induces the Diaphanous-2 molecule that facilitates the transport of capsid toward the nucleus via dynein motors (3)(4)(5)(6)(7)(8). KSHV-induced ERK and NF-κB are essential for the initiation of viral gene expression.…”
mentioning
confidence: 98%
See 3 more Smart Citations